2022
DOI: 10.28991/cej-2022-08-02-09
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Pounding Response of Neighboring Structure using Various Codes with Soil-Structure Interaction effects: Focus on Separation Gap

Abstract: Due to the high cost and less availability of land, the buildings are constructed adjacent to each other with a significantly smaller separation gap. Whenever seismic forces act on adjacent structures, they collide and cause significant structural and architectural damage. Soil-Structure Interaction (SSI) effects cause more complications in the adjacent structures. This paper assesses the gap distance between RC bare frame adjacent structures of varying heights in medium and soft soil with and without SSI to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
3
0
0
Order By: Relevance
“…Overall, the study shows that the soil-structure interaction has a significant impact on the behavior of buildings during earthquakes, and the type of soil and bracing system used can greatly affect the safety of the structure. Furthermore, a recent study focused on soil-structure interaction of adjacent buildings has shown that by considering soil-structure interaction, there is an increase of 90 to 95% in the maximum lateral roof displacement values, which is consistent with our findings [42]. It is essential to consider the inter-story drift ratio and lateral displacement in structural design and stability verification, and to account for the effects of soil-structure interaction in seismic design.…”
Section: Lateral Displacementsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the study shows that the soil-structure interaction has a significant impact on the behavior of buildings during earthquakes, and the type of soil and bracing system used can greatly affect the safety of the structure. Furthermore, a recent study focused on soil-structure interaction of adjacent buildings has shown that by considering soil-structure interaction, there is an increase of 90 to 95% in the maximum lateral roof displacement values, which is consistent with our findings [42]. It is essential to consider the inter-story drift ratio and lateral displacement in structural design and stability verification, and to account for the effects of soil-structure interaction in seismic design.…”
Section: Lateral Displacementsupporting
confidence: 91%
“…However, it was found that the time period increased when the effect of soil-structure interaction (SSI) was considered, and also when the bracing type was changed from column bracing to shear wall bracing. These findings were also demonstrated in a recent study, where the consideration of SSI effect resulted in a 15-25% increase in time period [42]. Consequently, it has become imperative to incorporate structural ductility in the design to cater to the increased time period.…”
Section: Time Periodsupporting
confidence: 54%
“…Therefore, the study highly recommends performing similar studies for buildings with mat foundation systems. Similar findings from (Elwardany et al, 2019;Jaradat et al, 2021;Awchat et al, 2022) emphasized the importance of including SSI effects in the calculation for the pounding impacts.…”
Section: Wall-frame Structuressupporting
confidence: 61%